Dangerous Knowledge: The Political, Personal, and Epistemological Promise of Feminist Research in Management and Organization Studies. (29th March 2020) - Bell, Emma; Meriläinen, Susan; Taylor, Scott; Tienari, Janne
Abstract: Feminism is a theoretical perspective and social movement that seeks to reduce, and ultimately eradicate, sexist inequality and oppression. Yet feminist research remains marginal in the most prestigious management and organization studies (MOS) journals, as defined by the Financial Times 50 (FT50) list. Based on a review of how feminism is framed in these journals (1990–2018), we identify three overlapping categories of how feminism is represented: (i) as a conceptual resource which is used to address specific topics; (ii) as an empirical category associated with the study of specific types of organization or organizing practice; and, rarely, (iii) as a methodology for producing knowledge. While feminist knowledge exists beyond these parameters, such as in the journal Gender, Work & Organization, we suggest that the relative absence of explicitly feminist scholarship in the most prestigious MOS journals reflects an epistemic oppression which arises from the threat that feminism presents to established ways of knowing. Drawing on Sara Ahmed's work, we use the 'sweaty concept' of dangerous knowledge to show how feminism positions knowledge as personal, introducing a radical form of researcher subjectivity which relies on the acknowledgment of uncertainty. We conclude by calling for the epistemic oppression of feminist scholarship to be recognized and redressed so the potential of feminism as a way of knowing about organizations and management can be realized. This, we argue, would enable feminist research praxis in MOS to develop as an alternative location of, in bell hooks' term, healing that challenges the main/malestream.